2003
DOI: 10.1095/biolreprod.102.011056
|View full text |Cite
|
Sign up to set email alerts
|

A Differential Mechanism Is Involved During Heparin- and Cryopreservation-Induced Capacitation of Bovine Spermatozoa

Abstract: After ejaculation, mammalian spermatozoa must undergo capacitation to fertilize. Capacitation of bovine spermatozoa occurs in vitro in medium supplemented with heparin. Semen cryopreservation is an important tool for assisted reproduction, although the fertility of frozen-thawed spermatozoa is reduced, possibly due to precocious capacitation-like changes that are known to occur. Our purpose was to clarify the mechanisms involved in bull sperm cryocapacitation induced by cryopreservation. Our general hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(110 citation statements)
references
References 47 publications
12
97
0
1
Order By: Relevance
“…On the other hand, several studies have shown the capacity of genistein taken at a higher concentration to inhibit the progesterone-induced acrosome reaction [50][51][52]. Besides these differences related to concentration, another question to take into consideration is related to the possible different mechanisms for induced npg capacitation of fresh spermatozoa and cryocapacitation, as previously described in bull spermatozoa [53]. In the frozen bull spermatozoa, the genistein did not affect tyrosine phosphorylation [54], suggesting that cryopreservation affects the regulatory mechanism of capacitation [53,54].…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, several studies have shown the capacity of genistein taken at a higher concentration to inhibit the progesterone-induced acrosome reaction [50][51][52]. Besides these differences related to concentration, another question to take into consideration is related to the possible different mechanisms for induced npg capacitation of fresh spermatozoa and cryocapacitation, as previously described in bull spermatozoa [53]. In the frozen bull spermatozoa, the genistein did not affect tyrosine phosphorylation [54], suggesting that cryopreservation affects the regulatory mechanism of capacitation [53,54].…”
Section: Resultsmentioning
confidence: 95%
“…Results from our laboratory show that immediately after thawing numerous tyrosine phosphoproteins are already present (Fig. 6), suggesting that the signalling cascade leading to protein tyrosine phosphorylation is already activated (Cormier and Bailey 2003). Furthermore, the addition of heparin does not further increase tyrosine phosphorylation.…”
Section: )mentioning
confidence: 86%
“…Semen was processed identically. Straws were thawed, sperm incubated in capacitating medium with or without 15 µg mL -1 heparin for up to 5 h. No effect of the glucose treatment is evident as similar percentages of sperm are capacitated at thawing (0 h; P > 0.05; from Cormier and Bailey 2003). Fig.…”
Section: How Can Sperm Be Protected?mentioning
confidence: 99%
“…The situation of phosphorylated proteins at the principal piece of the flagellum has been related to motility hyperactivation and to the presence of A-kinase anchoring proteins (which anchor PKA) located in the fibrous sheath of the sperm flagellum in several species (Carrera et al 1996, Mandal et al 1999, Jha & Shivaji 2002a, Pommer et al 2003. Conversely, a capacitation-related redistribution of phosphotyrosine residues to the acrosome has been reported in humans (Naz et al 1991), boars (Tardif et al 2001, Dube et al 2005, bulls (Cormier & Bailey 2003) and buffalo (Roy & Atreja 2008). Moreover, other studies have revealed that certain tyrosine phosphoproteins become localized to the sperm surface overlying the acrosome during capacitation suggesting a key role of these proteins in sperm-zona binding (Asquith et al 2004, Piehler et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a capacitation-associated redistribution of phosphotyrosine residues to the acrosome has been reported in boars (Petrunkina et al 2001, Tardif et al 2001, bulls (Cormier & Bailey 2003) and buffalo (Roy & Atreja 2008), and specific phosphotyrosine proteins localized over the acrosomal region have been postulated to be involved in the zona pellucida interaction and/or fusion events (Leyton & Saling 1989, Naz et al 1991, Ficarro et al 2003, Dube et al 2005.…”
Section: Introductionmentioning
confidence: 99%